Digital library: today’s need- a review - Jadhav, Kavita Ajay (International Multidisciplinary Research Journal, 2011)
The library and information professionals are required to acquire such knowledge and skills as the library is one of the highly IT influenced service profession. Library and information professionals with IT skills are aimed at providing services that are expected of from the clientele in the new environment. This paper consists of digital library Advantage and disadvantages and function. This paper also highlights on the impact of information technology on the traditional library. Significance of use of Digital Library Software’s in building digital library environment and publication trends in Digital Libraries.